Transnational solidarity or conflict? Trade unions and neo-liberal restructuring in Europe. - Bieler, Andreas (2008)
It is frequently argued that European trade unions have been co-opted into the neo-liberal restructuring of the European social relations of production. The purpose of this paper is twofold: First, it will be assessed whether this allegation is actually justified. Second, the paper will review concrete examples of trade union cooperation opposed to neo-liberal restructuring on the one hand, as well as outline several areas of tensions within the European labour movement, which undermine potential transnational solidarity on the other. It will be argued that while trade unions are not automatically progressive actors vis-à-vis neo-liberal restructuring, they have the potential to play an important role in a wider resistance movement.